Bio-Based Valorization of Lignin-Derived Phenolic Compounds: A Review - Martínková, Ludmila; Grulich, Michal; Pátek, Miroslav; Křístková, Barbora; Winkler, Margit (Biomolecules, 2023)
Lignins are the most abundant biopolymers that consist of aromatic units. Lignins are obtained by fractionation of lignocellulose in the form of "technical lignins". The depolymerization (conversion) of lignin and the treatment of depolymerized lignin are challenging processes due to the complexity and resistance of lignins. Progress toward mild work-up of lignins has been discussed in numerous reviews. The next step in the valorization of lignin is the conversion of lignin-based monomers, which are limited in number, into a wider range of bulk and fine chemicals. These reactions may need chemicals, catalysts, solvents, or energy from fossil resources. This is counterintuitive to green, sustainable chemistry. Therefore, in this review, we focus on biocatalyzed reactions of lignin monomers, e.g., vanillin, vanillic acid, syringaldehyde, guaiacols, (iso)eugenol, ferulic acid, p-coumaric acid, and alkylphenols. For each monomer, its production from lignin or lignocellulose is summarized, and, mainly, its biotransformations that provide useful chemicals are discussed. The technological maturity of these processes is characterized based on, e.g., scale, volumetric productivities, or isolated yields. The biocatalyzed reactions are compared with their chemically catalyzed counterparts if the latter are available.
Keywords: rozpouštědla; eugenol; Catalysis; guaiacol; valorization; vanillin; alkyl phenols; Solvents; Phenols; biotransformation; lignin; Lignin; isoeugenol; p-coumaric acid; fenoly; katalýza; ferulic acid